How to Define a Systemically Important Financial Institution – A New Perspective - Volker Brühl (Intereconomics, 2017)
The recent financial crisis has demonstrated that a failure of systemically important financial institutions (SIFIs) could seriously damage the stability of the financial system. A precise and consistent definition of a SIFI is pivotal to ensure efficient and effective regulation of the global financial sector. This paper proposes a threefold test that indicates which financial institutions are systemically important across the various industry segments.
Keywords: 330